Dry eye syndrome: a disease of the civilization. diagnosis and treatment options - V. V. Brzhesky (Медицинский совет, 2013)
For many years now dry eye syndrome (DES) characterized by relatively high prevalence in the population of developed countries remains a challenge for practical medicine. The prevalence of DES continues to grow. According to the studies of R. Marquardt and F.N. Wenz dated 1980, up to 30% of all ophthalmic patients were affected by the eye disease then; based on our reports of today, the number already reached and exceeded 45% [1, 2]. The reasons of the incidence growth are explained by frequent cases of computer vision and office syndromes, increasing number of laser refractive surgeries and wide use of contact lenses for vision correction. The above-mentioned factors of civilization more typically affect young people for whom the symptoms are often the main reason of decline of visual capacity and in some cases even of forced change of occupation [1, 3, 5].